Reseña a… Álvarez, Yago (2023). Pescar el salmón. Bulos, narrativas y poder en la prensa económica. Madrid: Capitan Swing. (184 págs.). - Mansilla, Jose (Revista Andaluza de Antropología, 2023)
Reseña a… Álvarez, Yago (2023). Pescar el salmón. Bulos, narrativas y poder en la prensa económica. Madrid: Capitan Swing. (184 págs.).